THE SWITCHING BEHAVIOR DETERMINANTS OF SHARIA BANKING: ROLES OF GENDER AND EDUCATION - Siswanto; Nur Asnawi; Rini Safitri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to analyze the determinants of the switching behavior of Sharia banking. The primary data of the study was derived from questionnaires. Using a random sampling technique, the study employed a sample of 205 respondents. Data were analyzed using descriptive statistics, analysis of comparative and partial least square (PLS). The findings indicate that determinants of switching behavior are Sharia compliance, internet banking, and employee friendliness. Furthermore, it suggests that there are significant differences in the switching behavior of sharia banking customers based on gender and education. The variable of Sharia compliance affects the switching behavior directly, and the intention to switch serves as a full mediation variable. This research has managerial implications on the improvement of Sharia banking comprehension to the higher level of education through a rational approach.